2012
DOI: 10.7314/apjcp.2012.13.8.3709
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Ablation Guided by Contrast-enhanced Ultrasound in Treatment of Metastatic Hepatocellular Carcinoma after Liver Transplantation

Abstract: This study evaluated the advantages and applications of contrast-enhanced ultrasound (CEUS)-supported percutaneous radiofrequency ablation (RFA) in the treatment of metastatic hepatocellular carcinoma after liver transplantation, based on clinical details. CEUS-supported percutaneous RFA was adopted to treat 12 patients with hepatic metastatic carcinomas after liver transplantation. The diameters of the metastatic carcinomas varied from 1 cm to 5 cm, and the foci were discovered after 3 months to 12 months. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This indication is by far the largest subsection of CEUS‐guided procedures, and the use of CEUS in this regard falls into 3 categories: (1) CEUS visualization of the ablation target; (2) intraprocedural guidance and immediate postablation evaluation; and (3) ablation evaluation and follow‐up. A total of 25 articles were identified by the systematic search . They were all case series, and many had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indication is by far the largest subsection of CEUS‐guided procedures, and the use of CEUS in this regard falls into 3 categories: (1) CEUS visualization of the ablation target; (2) intraprocedural guidance and immediate postablation evaluation; and (3) ablation evaluation and follow‐up. A total of 25 articles were identified by the systematic search . They were all case series, and many had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies reported feasibility or technical success rates for CEUS‐guided percutaneous ablation in the range of 92% to 100%, and the rates of clinical or technical effectiveness, which was defined as immediate complete tumor necrosis, were 90% to 100% . Regarding immediate postablation assessments of treatments, a remarkably high benefit of CEUS was reported in a prospective feasibility study of 22 mixed liver malignancies using intraprocedural and immediate postablation CEUS assessments of tumor ablation during CT‐guided RF ablation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, if patients with HCC who were not candidates for surgical resection or liver transplantation underwent RFA, their 5-year overall survival rates could be improved to 37% (Llovet and Bruix 2000;Ioannou et al, 2008). Xin Dai et al (Dai et al, 2012) recently demonstrated that RFA also had the advantages of accurate localization, good efficacy, easy operation, and minimal invasion without any complications in the treatment of HCC recurrence after liver transplantation. In our study AFP, AFP-L3, and GP-73 levels all sharply decreased after RFA, which indicated that these tumor markers could reflect the tumor burden and demonstrate the efficacy of RFA.…”
Section: Discussionmentioning
confidence: 99%
“…With RFA alone, the melting range is limited (Ji and Xu, 2011;Dai et al, 2012;Hofer et al, 2008). When we injected 5% hypertonic saline, lidocaine or a mixed solution, increased ion concentrations were noted in the ablation areas.…”
Section: 5799 In Vivo Experimental Study On the Effects Of Fluid In mentioning
confidence: 99%